2015
DOI: 10.5958/0974-0279.2015.00006.3
|View full text |Cite
|
Sign up to set email alerts
|

Supply Response of Horticultural Crops: The Case of Apple and Pear in Jammu & Kashmir

Abstract: The apple and pear have a significant place in the horticulture sector of Jammu & Kashmir. The planted areas have been expanding quiet significantly since 1990s. Advanced technologies for these crops have been rationalized and adopted by the growers; however, seasonal and annual variations of the fruit supplies continue to characterize prices at both wholesale and consumption levels. In this study, Nerlovian model has been used to estimate supply response, Engle-Granger test and Vector Error Correction Model h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
5
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 4 publications
3
5
2
Order By: Relevance
“…An increase in price renders less than proportionate increase in market arrival of apples. This price inelasticity is also reported by earlier studies of Wani et al (2015) and many other international supply response studies like Rude and Surry (2014), Rezitis and Stavropoulos (2009). Again, the competitive fruit price elasticity of market arrival of apples in both long-run and short-run is statistically insignificant.…”
Section: Long-run and Short-run Elasticitiessupporting
confidence: 78%
See 3 more Smart Citations
“…An increase in price renders less than proportionate increase in market arrival of apples. This price inelasticity is also reported by earlier studies of Wani et al (2015) and many other international supply response studies like Rude and Surry (2014), Rezitis and Stavropoulos (2009). Again, the competitive fruit price elasticity of market arrival of apples in both long-run and short-run is statistically insignificant.…”
Section: Long-run and Short-run Elasticitiessupporting
confidence: 78%
“…In this study, the estimated long-run and short-run price elasticities of supply of apple reveal that the long-run elasticities are greater in magnitude than the short-run elasticities indicating that the apple growers strongly respond to price and form their expectations over long-run. This result contradicts that of Wani et al (2015) but is supported by earlier results of Chembezi (1991), Holt and Moschini (1992) and many other studies that report a greater magnitude of long-run elasticities over short-run price elasticities. Wani et al (2015) reported the same degree of elasticity in both long-run and short-run.…”
Section: Long-run and Short-run Elasticitiescontrasting
confidence: 51%
See 2 more Smart Citations
“…The alternative approach to study the supply response of crops was the use of co-integration analysis and VECM (Haq and Arshad, 2010;McKay, 1999;Thiele, 2000;Wani et al, 2015). Hence, VECM were applied to estimate the supply response elasticity for groundnut crop in Karnataka state.…”
Section: Analysis Tools Used: Vector Error Correction Model (Vecm) Momentioning
confidence: 99%